CT 검사에서 혈관외유출 예방을 위한 EDA 시스템의 실험적 연구 - 권대철 (The Graduate School, Ajou University, 2005)
Subcutaneous extravasation of the radiographic contrast media is one of the complications of the contrast medium-enhanced procedures. Automated power injectors enable the contrast material to be delivered at a uniform high-flow-rate and as a nonfragmented bolus, and this is essential formany contrast material-enhanced CT applications.The major risk associated with the use of automated power injectors is the well known complication of contrast material extravasation at the injection site.Automated injection of computed tomography (CT) contrast material can produce the compartment syndrome. Selection of the nonionic contrast material after careful evaluation of the intravenous administration site and monitoring of the patient during the use of a mechanical power injector may helpminimize or prevent extravasation injuries. We wanted to assess the ability of an Extravasation Detection Accessory (EDA) to detect the clinically important extravascular injection of iodinated contrast material that was delivered with an automated mechanical power injector. The purpose of this study was to assess the ability of this device during clinically important episodes of extravasation. The EDA system was composed of a straing age, an amplifier and acomputer based system. A strain gage pliable adhesive patch was applied to the skin over the intravenous catheter and the catheter was connected to the power injector with a cable to monitor the resolution data. If the programmed monitoring, which was developed with MS Visual C++, at the extravasation occurred, then the injection was interrupted the auto injector. CT was used to demonstrate the clinically important extravasation. Monitoring with the EDA system was successfulin the previous animal and human studies. This study was a prospective, observationa lstudy in which the EDA system was used to monitor the automated mechanical injection of contrast material in 7 rabbits, 4 dogs and 156 human patients. In the rabbit experimental cases,there were seven true-positive cases(range of the extravasation volumes:14-23 mL). The algorithm results showed seven true-positive cases (range of the extravasation volumes: 7-16 mL), nineteen true-negative cases, two false-positive cases and no false-negative cases.The EDA system had a sensitivity of 100% and a specificity of 90% for the detection of clinically important extravasation. For the dogs, there were two true-positive cases (range of extravasation volumes:18-22 mL),twenty three true-negative cases,three false-positive cases and no false-negative cases.The EDA system had a sensitivity of 100% and a specificity of 88% for the detection of clinically important extravasation. 156 patients referred for contrast enhanced body computed tomography were examined in a prospective, observation study in which the EDA system was used to identify and interrupt to any injection associated with clinically important extravasation. The presence or absence of extravasation was definitively established with performing helical CT at the injection site.There were two true positive cases (range of extravasation volumes:22-25 mL).The EDA system had good sensitivity for the detection of clinically important extravasation and the EDA system has the clinical potential for the early detection of extravasation of the contrast medium that is administered with power injectors. The EDA system is easy to use,safe and accurate for the monitoring extravasation of the intravenous injections, and this system may prove especially useful in CT applications.
학위논문(박사)--亞洲大學校 大學院 :의용공학과정,2005. 8
Keywords: 혈관외유출; 조영제; 스트레인 게이지; EDA 시스템